Marginal Discrepancy of Cast Copings to Abutments with Three Different Luting Agents - Rosas Díaz, José (2019)
Aim. +e purpose of this study was to evaluate the MD (marginal discrepancy) on the calcinable copings in abutments for cemented prostheses with three luting agents. Methods. Sixty-four analogs of CeraOne-type abutments (NACONIH code, Titanium Fix Implant Sytem SP, Brazil) were divided into four groups (n = 16). +e copings were cast and placed on the CeraOne abutment analogs and cemented with eugenol-free zinc oxide (EfZO) (n = 16), with glass ionomer (GI) (n = 16), and with zinc phosphate (ZP) (n = 16), and as a control group, there were CeraOne plastic copings (NACOC code, Titanium Fix Implant Sytem SP, Brazil) (n = 16) which were not cemented with any material. After 24 hours, theMDof the four groups was measured.MDwas evaluated using a stereoscopic microscope (Leica EZ4 W, Leica Microsystems, Germany) with an increase of ×100. MD was measured at four predetermined and equidistant sites with respect to the marginal line of the cast adaptation. +e measurement was made from the distance between the free edge of the cast cylinder and the margin of preparation of the titanium abutment, with a level of statistical significance of p < 0.05. Results. Of the three fixing agents, the ZP was found to have the highest MD (53.59 ± 14.21 μm); however, the lowest MD (41.72 ± 9.10 μm) was found in the GI group. +ese differences are statistically significant at p < 0.001. Conclusions. In summary, according to our results, it was found that ZP cement showed the highest MD after cementation, followed by the glass ionomer, while EfZO showed the lowest MD.